Analysis of Risk Factors Influencing the Incidence of Hemorrhagic Stroke in People Aged 35-70 Years at Banyumas Regional Hospital - Rachmawati, Farras; Rejeki, Dwi Sarwani Sri; Wahyuningsih, Eri; Radi, Radi (Department of Public Health, Faculty of Health Sciences, Jenderal Soedirman University, 2024)
Background: Stroke is one of the non-communicable diseases with the highest mortality rate in the world. Hemorrhagic stroke is a type of stroke caused by a rupture of blood vessels in the brain that can threaten the lives of patients. Mortality and morbidity caused by hemorrhagic stroke are higher than ischemic stroke. This study aims to determine what risk factors cause hemorrhagic stroke. Methods: This study is a quantitative analytical study with a case-control study design conducted at Banyumas Regional Hospital. The study sample consisted of 100 case samples of hemorrhagic stroke patients and 100 control samples of ischemic stroke patients using random sampling techniques. This study was conducted in September-October 2024. The variables studied were age, gender, ancestry, history of hypertension, history of DM, dyslipidemia, smoking habits, diet, physical activity, obesity, and control compliance. The research data consisted of secondary data obtained from the medical records section of Banyumas Regional Hospital and primary data obtained through interviews using questionnaires. Data analysis used SPSS 23 software with univariate tests, bivariate with chi-square, and multivariate with logistic regression to calculate the odds ratio (OR). Results: The average age of the study respondents was 57.4 years and female. Variables that influenced the incidence of hemorrhagic stroke were non-compliance with control (p-value 0.000 and OR of 4.869), history of hypertension (p-value 0.004 and OR of 3.110), and poor diet (p-value 0.015 and OR of 2.204). Variables that did not influence were age, gender, heredity, history of DM, dyslipidemia, smoking habits, physical activity, and obesity. Conclusions: Patients who have a history of hypertension, poor diet, and are not compliant with medication controls are at greater risk of suffering from hemorrhagic stroke. Keywords: Hemorrhagic Stroke, Control Compliance, Hypertension History, Diet